Three-dimensional resistivity modelling and interpretation of geothermal fields in the Gediz graben by magnetotellurics - Cengiz, Özlem. (Thesis (Ph.D.)-Bogazici University. Kandilli Observatory and Earthquake Research Institute, 2018., 2018)
The Gediz Graben hosting several geothermal systems is one of the most promising grabens in terms of temperature and production rate of western Anatolia. In order to provide the most comprehensive understanding about the geothermal systems situated in the graben, specifically about the reservoir types, heat sources and structural controls, 253 MT sites were installed at four different areas of the graben to delineate the electrical resistivity distribution at depth. The wide-band MT data were analyzed by phase tensor analysis, and then the data at 31 selected periods in the range from 0.001 s to 1000 s modeled in three-dimensions (3D). The resulting models reveal three different reservoir types, namely (i) a classical geoelectrical distribution of a high temperature geothermal system, with a prominent highly conductive hydrothermal alteration zone sitting above a more resistive deep reservoir zone, (ii) a deep reservoir zone characterized by fractures within metamorphic rocks in the highly resistive basement and (iii) a shallow reservoir (aquifer) corresponding to the hot springs in the shallow sedimentary layer existing in the Gediz Graben. The heat source of the geothermal systems may be attributed to the heat transfer from the interior of the Earth to the upper crust as a consequence of crustal thinning resulted from the extensional tectonics accompanied by magma intrusions into crust in western Anatolia. The 3D models bring out a well-defined interface between the sedimentary cover and underlying metamorphic basement owing to high resistivity contrast between two layers, characterizing the Gediz detachment fault (GDF). The geothermal fields formed along the southern margin of the graben are spatially coincident with the intersecting zone of two fractures, namely the GDF and high angle normal faults, and the circulation of geothermal fluids in reservoirs are dominantly controlled by these fractured zones and major faults. The crustal scale main graben-bounding fault (MGBF) acts as a conduit through which fluids and heat are transported from deeper parts of the crust to near surface. The meteoric waters percolating deep into the crust through the north dipping normal faults are probably heated up by magmatic intrusions, and some of geothermal waters containing meteoric and magmatic fluids rise up to surface through the permeable faults, in particular through the lower bounding sub-horizontal GDF. Furthermore, 3D resistivity models suggest a thick sedimentary layer (2500-3000 m) in the middle part of the graben basin. The thickness of the sedimentary layer decreases gradually on the northern and southern margins of the graben and becomes much thinner towards the eastern end of the graben. 3D resistivity models also delineate an undulating basement topography under the conductive sedimentary fill of the graben.
Keywords: Geothermal resources -- Turkey -- Gediz.